Correction to: Studies on H2-Assisted Liquefied Petroleum Gas Reduction of NO over Ag/Al2O3 Catalyst - Pratichi Singh; Deepak Yadav; Pooja Thakur; Jitendra Pandey; Ram Prasad (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
Correction to: Bulletin of Chemical Reaction Engineering & Catalysis (2018), 13 (2): 227-235 (doi:10.9767/bcrec.13.2.1307.227-235)An error appeared in Corresponding Author in a paper entitled “Studies on H2-Assisted Liquefied Petroleum Gas Reduction of NO over Ag/Al2O3 Catalyst” published in Bulletin of Chemical Reaction Engineering & Catalysis. The Corresponding Author is corrected to be:* Corresponding Authors. Tel: +919415268192. Email: rprasad.che@itbhu.ac.in (R. Prasad) Tel: +917505072607. Email: dyadav.rs.che13@iitbhu.ac.in (D. Yadav)——————The original article can be found online at: https://doi.org/10.9767/bcrec.13.2.1307.227-235——————Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).How to Cite: Singh, P., Yadav, D., Thakur, P., Pandey, J., Prasad, R. (2020). Correction to: Studies on H2-Assisted Liquefied Petroleum Gas Reduction of NO over Ag/Al2O3 Catalyst. Bulletin of Chemical Reaction Engineering & Catalysis, 15 (2): 603-603 (doi:10.9767/bcrec.15.2.7659.603-603)Permalink/DOI: https://doi.org/10.9767/bcrec.15.2.7659.603-603